2022
DOI: 10.1136/bmjopen-2021-058026
|View full text |Cite
|
Sign up to set email alerts
|

Towards a cervical cancer-free future: women’s healthcare decision making and cervical cancer screening uptake in sub-Saharan Africa

Abstract: ObjectiveWe investigated the association between women’s healthcare decision making and cervical cancer screening uptake in sub-Saharan Africa.DesignSecondary data from the Demographic and Health Surveys of six countries in sub-Saharan Africa were used. We employed multilevel binary logistic regression modelling.SettingSub-Saharan Africa.ParticipantsWomen aged 15–49 years in Benin (n=5282), Côte d’Ivoire (n=1925), Cameroon (n=7558), Kenya (n=6696), Namibia (n=1990) and Zimbabwe (n=5006).Primary outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The women who made their own decisions were more knowledgeable on risk factors, most educated and younger than the two groups. This is in agreement with another study on women’s healthcare decision making and cervical cancer screening uptake done in 4 countries in SSA, which showed that women who are able to make autonomous healthcare decisions were most likely to uptake cervical cancer screening followed by those who decided in partnership with their husbands and least of all were those whose decisions were solely made by their husbands [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The women who made their own decisions were more knowledgeable on risk factors, most educated and younger than the two groups. This is in agreement with another study on women’s healthcare decision making and cervical cancer screening uptake done in 4 countries in SSA, which showed that women who are able to make autonomous healthcare decisions were most likely to uptake cervical cancer screening followed by those who decided in partnership with their husbands and least of all were those whose decisions were solely made by their husbands [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…We also found that women with lower educational attainment were less likely to be aware of facilities that provide cervical cancer screening services. This is not surprising as higher educational attainment tends to empower women to access information including health information such as where to access cervical cancer screening services (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained from the perspective that higher maternal education predisposes or exposes women to health information and services that tend to increase their knowledge about the nature and importance of protecting themselves against tetanus, hence encouraging the uptake of preventive interventions such as the tetanus toxoid vaccine. Another possible explanation could be that mothers with a higher level of education are likely to be empowered to make autonomous decisions about their healthcare, 19 , 20 including taking actions to protect themselves from tetanus.…”
Section: Discussionmentioning
confidence: 99%